Health systems resilience in managing the COVID-19 pandemic: lessons from 28 countries - Haldane, Victoria; De Foo, Chuan; Abdalla, Salma M.; Jung, Anne-Sophie; Tan, Melisa; Wu, Shishi; Chua, Alvin; Verma, Monica; Shrestha, Pami; Singh, Sudhvir; Perez, Tristana; Tan, See Mieng; et al. (Nature medicine, 2021)
Health systems resilience is key to learning lessons from country responses to crises such as coronavirus disease 2019 (COVID-19). In this perspective, we review COVID-19 responses in 28 countries using a new health systems resilience framework. Through a combination of literature review, national government submissions and interviews with experts, we conducted a comparative analysis of national responses. We report on domains addressing governance and financing, health workforce, medical products and technologies, public health functions, health service delivery and community engagement to prevent and mitigate the spread of COVID-19. We then synthesize four salient elements that underlie highly effective national responses and offer recommendations toward strengthening health systems resilience globally. A review of COVID-19 responses in 28 selected countries identifies elements of highly effective public health responses and offers recommendations toward strengthening health systems resilience.